Evolution of sleep phylogenetic and functional perspectives - Barton, Robert A. 1959-; McNamara, Patrick 1956-; Nunn, Charles L. (Cambridge University Press, 2010)
Research during the past two decades has produced major advances in understanding sleep within particular species. Simultaneously, molecular advances have made it possible to generate phylogenetic trees, while new analytical methods provide the tools to examine macroevolutionary change on these trees. These methods have recently been applied to questions concerning the evolution of distinctive sleep state characteristics and functions. This book synthesizes recent advances in our understanding of the evolutionary origins of sleep and its adaptive function, and it lays the groundwork for future evolutionary research by assessing sleep patterns in the major animal lineages.